Analisa Risk Priority Number (RPN) Terhadap Keandalan Komponen Mesin Thresher dengan Menggunakan Metode FMEA Di PT. XYZ - Satria Buana Marpaung; Din Aswan Amran Ritonga; Ade Irwan (Universitas Harapan Medan, 2021)
PT. XYZ is a palm oil factory (PKS) producing crude palm oil (CPO). PT. XYZ has not implemented an effective engine maintenance system. The maintenance system that has been implemented is corrective maintenance, which is making repairs when there is damage. In addition, it is also assisted with planned maintenance that is scheduled every week to clean production machines. Therefore it is necessary to identify machine components that are susceptible to damage (critical components) and it is necessary to take special care measures for critical machine components by implementing a predective maintenance schedule (Prevention). Simulation techniques, often known as Monte Carlo simulation, estimate reliability using sampling random scenario. Failure mode effect analisys (FMEA) is defined as a process used to determine the actions that should be taken to ensure that each physical item or a system can run properly according to the function desired by the user then based on data processing, replacement of the roller binding drum binding drum , angle iron welding, chain transmission component replacement, drum stopper bearing replacement. Replacement of the drum stopper bolt, replacement of the chain transmission part is very loose and the replacement of the iron is carried out in corrective maintenance (replacement of components after damage occurs). And the results at the lowest value on the thresher engine component are in the Loose Transmission Chain component, the repair rate is 0.5 hours and the number is 0.999737189. Based on the results of the analysis of numbers (availability), the highest number is found in Broken Elbow Iron with a repair rate of 3 hours and the number 0.999605833